Evaluation of the potential anti-inflammatory and neuroprotective effect of a FAAH inhibitor in glaucome models - Martins, Joana Margarida Cardoso Serra (2015)
Dissertação de mestrado em Biotecnologia Farmacêutica, apresentada à Faculdade de Farmácia da Universidade de Coimbra